2008
DOI: 10.1016/j.biopsych.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Glial Glutamate and Aspartate Transporter (Excitatory Amino Acid Transporter 1) Causes Locomotor Hyperactivity and Exaggerated Responses to Psychotomimetics: Rescue by Haloperidol and Metabotropic Glutamate 2/3 Agonist

Abstract: Background-Recent data suggest that excessive glutamatergic signaling in the prefrontal cortex may contribute to the pathophysiology of schizophrenia, and that promoting presynaptic glutamate modulation via group II metabotropic glutamate (mGlu2/3) receptor activation can exert antipsychotic efficacy. The glutamate transporter GLAST (EAAT1) regulates extracellular glutamate levels via uptake into glia, but the consequences of GLAST dysfunction for schizophrenia are largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 23 publications
3
80
0
Order By: Relevance
“…More specifically, these studies revealed a link between a high-risk GRM3 allele and reduced expression of glial glutamate transporter. Although there is not much further evidence in support of this hypothesis, a genetic silencing of glial transporter expression in mice resulted in the behavioral abnormalities that are typically observed after the treatment with psychotomimetic drugs (Karlsson et al, 2008). The most intriguing is perhaps that these behaviors were effectively antagonized by the stimulation of mGlu2/3 receptors.…”
Section: Mglu2/3 Receptor Agonistsmentioning
confidence: 99%
“…More specifically, these studies revealed a link between a high-risk GRM3 allele and reduced expression of glial glutamate transporter. Although there is not much further evidence in support of this hypothesis, a genetic silencing of glial transporter expression in mice resulted in the behavioral abnormalities that are typically observed after the treatment with psychotomimetic drugs (Karlsson et al, 2008). The most intriguing is perhaps that these behaviors were effectively antagonized by the stimulation of mGlu2/3 receptors.…”
Section: Mglu2/3 Receptor Agonistsmentioning
confidence: 99%
“…Furthermore, previous research indicates antipsychotics act pharmacologically on the glutamate system resulting in molecular as well as physiological consequences and thereby may influence therapeutic outcome [Riva et al, 1997;Tascedda et al, 2001;Goff et al, 2002]. Karlsson and group reported excessive glutamatergic signaling in the prefrontal cortex that promotes presynaptic glutamate modulation mGlu2/3 receptors activation suggesting these receptor may exert antipsychotic efficacy [Karlsson et al, 2008].…”
Section: Introductionmentioning
confidence: 98%
“…Such a selective loss of GLT-1/EAAT-2 occurs in patients suffering from ALS (Rothstein et al 1995) and was further noted in mice over-expressing mutant huntingtin (Behrens et al 2002;Bradford et al 2009). Finally, recent studies pinpointed GLAST/EAAT-1 as a putative risk factor for schizophrenia (Karlsson et al 2008(Karlsson et al , 2009Walsh et al 2008).…”
Section: Discussionmentioning
confidence: 98%